Queering public policy: the LGBTQ movement influence on policymaking in Brazil - Galego, Diego Henrique (2022)
After the Brazilian democratisation in 1985, the LGBTQ movement deployed several strategies to influence the legislature to approve an LGBTQ bill in Congress but failed. Given the legislative inertia, the LGBTQ movement shifted strategies and venues of activism from legislative to executive and later to the judiciary. The federal executive and judiciary have created palliative policies to compensate for the legislative vacuum and tackle LGBTQ issues, particularly anti-discrimination policies. Therefore, this research raises the question: how does the LGBTQ movement influence policymaking in Brazil? By analysing the anti-homophobia policy process that started in 2001 in Congress and concluded with a judicial decision in 2019, this dissertation seeks to unpack a causal mechanism of influence between the LGBTQ movement and policymaking in one of the most violent countries for LGBTQ people globally. The interplay between social movement, public policy and queer theory helped investigate the movement-policy relationship in a Global South case study. Using data triangulation – document analysis, semi-structured interviews and Court cases analysis –allowed us to identify and analyse actors, events, decision-making, instruments and strategies driving the mechanisms of influence in the policy process.